Study on fish diversity and need for their conservation of Bakara River, Morang district, eastern Nepal - Yadav, Shiva Narayan (Nepalese Journal of Biosciences, 2016)
Forty eight fish species were collected in the present study. The population status of important fishes Chagunius chagunio and Channa striatus were found to be threatened. Mastacembulus puncalus was vulnerable and Clupisoma garua and Puntius ticto threatened because of pollution.